A life assessment for steam turbine rotor subjected to thermo-mechanical loading using inelastic analysis - Choi, W. S.; Fleury, E.; Song, G. W.; Hyun, J. S. (Experimental Mechanics in Nano and Biotechnology, Pts 1 and 2, 2006)
An important characteristic of a steam power plant is its ability to maintain reliability and safety of the plant against frequent start-ups and load changes. Transient regimes arising during start-ups, shut-downs and load changes give rise to unsteady temperature distribution with time in steam turbine rotor(HP/IP), which results in non-uniform strain and stress distribution. The rapid increase of temperature and rotational speed during starts-ups, especially, makes conditions more severe and causes main components' damage and reduction of life span for steam turbine. Thus accurate knowledge of thermal and centrifugal stresses are required for the integrity and lifetime assessment for the turbine rotor. So far, only elastic calculations are currently performed for simplicity. However, it is well known that the materials of steam turbine rotor deform inelastically at high temperature. Existing models proposed to describe the viscoplastic(rate-dependent) behavior are rather elaborate and difficult to incorporate with computer simulations in the case of complex structures. In this paper, the life assessment for steam turbine rotor was established by combining the inelastic behavior and the finite element method. The inelastic analysis was particularly focused on viscoplastic behavior that is simple enough to be used effectively in computer simulation and matches the essential features of the time-dependent inelastic behavior of materials reasonably well for cyclic loading under non-isothermal conditions. Using this study, life consumption of steam turbine rotor can be obtained.